The Arab critical scene in light of interactivity: reality and prospects - mabroukia, henia; mansour, amel (El Omda in Linguistics and Discourse Analysis, 2025)
The history of human civilizations has witnessed major historical junctures, leading to radical transformations of human thought. This contributed to the product of new cultural contexts, whereby all walks of life changed in interaction with the technological revolution and its digital products, New literary forms have emerged, curving their convoy from the paper medium, Settled in the dead of the machine and its applications, it renewed its creative tools and means, to show so-called digital writing in the midst of digital interactive criticism and how to receive interactive texts, The problems posed by his site in the Arab literary arena in order to obtain an interactive reading appropriate to the mercury of the interactive texts under the receipt process.